2017
DOI: 10.5539/jms.v7n2p27
|View full text |Cite
|
Sign up to set email alerts
|

The Inter Business Index Developing a Tool for Measurement and Comparability of Holistic Sustainability in Businesses

Abstract: The scope of sustainable development is undoubtedly growing, and becoming increasingly more important due to the process of globalization, amounting in complex environmental, societal and economic issues. Although the subject of business sustainability has been gaining traction and resulted in increased knowledge in the field, the business sustainability discourse is still at a young stage, where the different streams of approaches, definitions, systems and measures are fragmented and challenged. Today's globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The Inter Business framework focuses on analyzing the integration of sustainability in priorities, stakeholder dialogue and external communication of the company-bringing about a holistic view of the future preparedness of any company, market or sector analyzed (Hallin et al, 2017 stakeholders and communications the Index determines how well a company integrates the four abilities in their strategy by applying a qualitative analysis to the material. The analysis is in part based on a set of 12 indicators-values, strategy, main services, results, approach, priorities, transparency, sustainability context, stakeholder inclusiveness, key assets, diversity in board and corporate governance-and in part one additional measurement aimed at each capability as it is manifested in relationship to stakeholders (Hallin et al, 2017).…”
Section: The Inter Business Index Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Inter Business framework focuses on analyzing the integration of sustainability in priorities, stakeholder dialogue and external communication of the company-bringing about a holistic view of the future preparedness of any company, market or sector analyzed (Hallin et al, 2017 stakeholders and communications the Index determines how well a company integrates the four abilities in their strategy by applying a qualitative analysis to the material. The analysis is in part based on a set of 12 indicators-values, strategy, main services, results, approach, priorities, transparency, sustainability context, stakeholder inclusiveness, key assets, diversity in board and corporate governance-and in part one additional measurement aimed at each capability as it is manifested in relationship to stakeholders (Hallin et al, 2017).…”
Section: The Inter Business Index Methodsmentioning
confidence: 99%
“…The Inter Business Index is a tool for measurement of holistic value creation in business, providing comparable results over sectors and time. It is based on an identified gap, that corporate sustainability as understood today is context-specific and unable to take on our shared complex and difficult societal challenges, at the same time as higher demands are placed on businesses to do their part of solving them (Hallin et al, 2017).…”
Section: The Inter Business Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…Research done by the Inter Business Initiative propose a holistic view of sustainability, business and their value creation as one way forward when developing truly sustainable structures. Through published research we have found four abilities or key-components to be of utmost importance when working towards a holistic sustainability agenda; purpose, empathy, systems approach and transformation (Hallin et al, 2017). Understanding the value that companies bring to the world, and understanding their place in the system, how they affect all stakeholders, having the ability to build relationships and understand the information found there as well as having the ability to transform at in relation to a changing environment proved important for company success for future preparedness.…”
Section: Holistic Value Creationmentioning
confidence: 99%